2018
DOI: 10.1371/journal.pone.0199544
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty modulated exploration in the trade-off between sensing and acting

Abstract: Many sensorimotor activities have a time constraint for successful completion. In this case, any time devoted to sensory processing is at the expense of time available for motor execution. Earlier studies have explored how this competition between sensory processing and motor execution is resolved by using experimental designs that segregate the sensing and acting phase of the task. It was found that participants switch from the sensing to the acting stage such that the overall (sensorimotor) uncertainty in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 36 publications
1
7
1
1
Order By: Relevance
“…For healthy controls the slopes were positive for both the predicted minimal sensorymotor uncertainty [t(9) = 4.75, p < 0.005] and the shallowness of the valley [t(9) = 5.51, p < 0.001]. This is in line with our earlier findings in young subjects (Sengupta et al, 2018). By contrast, in the PD group only the correlation between switching time and shallowness of the valley was positive [t(8) = 2.79, p < 0.05], while the correlation with minimal sensory-motor uncertainty was not significantly different from zero [t(8) = -0.38, p = 0.7].…”
Section: Variability In Switching Timesupporting
confidence: 90%
See 3 more Smart Citations
“…For healthy controls the slopes were positive for both the predicted minimal sensorymotor uncertainty [t(9) = 4.75, p < 0.005] and the shallowness of the valley [t(9) = 5.51, p < 0.001]. This is in line with our earlier findings in young subjects (Sengupta et al, 2018). By contrast, in the PD group only the correlation between switching time and shallowness of the valley was positive [t(8) = 2.79, p < 0.05], while the correlation with minimal sensory-motor uncertainty was not significantly different from zero [t(8) = -0.38, p = 0.7].…”
Section: Variability In Switching Timesupporting
confidence: 90%
“…Within the sensory-motor tradeoff framework (using equation 4), we can only compute the optimal switching time, i.e., the time point at which an ideal observer would start acting, but does not explain variability around the optimal switching time. In our earlier work (Sengupta et al, 2018) we found that the variability in switching time correlated with parameters derived from the optimal sensory-motor noise tradeoff framework (equations 1-4). We follow the same approach here and correlate the observed variability in switching time with the predicted minimal sensory-motor uncertainty σ combined (t optimal ) on each trial.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Há evidências de que a atenção relaciona-se à qualidade do processo decisório em contextos como detecção de predadores, competição, comunicação e aprendizado social (RANGE et al, 2009;BEAUCHAMP, 2010 O processo decisório tem sido amplamente investigado, posto que resulta de um sofisticado mecanismo neurobiológico de "acoplamento" entre a percepção sensorial e a ação motora. Este fenômeno, denominado transformação sensoriomotora é profundamente conhecido em animais vertebrados e invertebrados, e está intimamente relacionado à eficiência dos comportamentos de fuga e alimentação (CARD; DICKINSON, 2008;HOFMANN et al, 2013;BAR et al, 2015;TOMASSINI;MORRONE, 2016;SENGUPTA et al, 2018). Em animais vertebrados, a transformação sensoriomotora é um fenômeno reconhecidamente variável, dependente do contexto e experiência (HANES;SCHALL, 1996).…”
Section: Discussionunclassified